Synthesis of graphene-based Co-B catalyst via simultaneous chemical reduction for hydrolysis of sodium borohydride - Ozdemir, Oguz Kaan; Hasimoglu, Aydin; Ahsen, Ali Sems (AMER INST PHYSICS, 2013)
Co-B nanoparticles are deposited on graphene sheets by simultaneous chemical reduction of Co+2 and graphite oxides using NaBH4 as the reducing agent. The reduced Co-B/graphene nanocomposites were characterized by X-ray diffraction, Fourier transform infrared spectra, X-ray photoelectron spectroscopy, and thermogravimetric analysis. The results show that after reduction, not only considerable amount of functional groups has been removed but also exhibited formation of Co-B alloy on the graphene sheets. The catalytic activity of nanocomposites was investigated by the hydrolysis of NaBH4 in aqueous solution. Graphene support material greatly enhances the hydrolysis of NaBH4 with respect to graphite and active carbon supports, and chemical reduced graphene sheets can readily form stable aqueous colloids through electrostatic stabilization. The present method is promising for the synthesis of effective supported catalysts for hydrolysis of NaBH4. (C) 2013 AIP Publishing LLC.
Keywords: HYDROGEN GENERATION; NABH4 SOLUTION; NI-P; COBALT; EFFICIENT; OXIDE; FILMS; PHOTOELECTRON; SUPPORT; NICKEL; Science & Technology - Other Topics; Energy & Fuels